2010
DOI: 10.1074/jbc.m110.163485
|View full text |Cite
|
Sign up to set email alerts
|

An Exceptionally Potent Inducer of Cytoprotective Enzymes

Abstract: The Keap1/Nrf2/ARE pathway controls a network of cytoprotective genes that defend against the damaging effects of oxidative and electrophilic stress, and inflammation. Induction of this pathway is a highly effective strategy in combating the risk of cancer and chronic degenerative diseases, including atherosclerosis and neurodegeneration. An acetylenic tricyclic bis(cyano enone) bearing two highly electrophilic Michael acceptors is an extremely potent inducer in cells and in vivo. We demonstrate spectroscopica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
59
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 100 publications
(60 citation statements)
references
References 39 publications
1
59
0
Order By: Relevance
“…33c Variable temperature NMR also demonstrated the reversibility of the reaction, as 411 was regenerated upon heating of the DTT- 411 adduct. 33c Other cyanoenones, such as tricyclic TBE-31 ( 434 ) 149 and monocyclic compounds 435-437 , 150 have shown similar reactivity towards thiols using the same UV and 1 H NMR methods (Figure 35). Surprisingly, compounds 439-440 showed no reactivity with DTT and 441-442 showed greatly reduced reactivity requiring 10 equiv of DTT for adduct formation, thereby demonstrating the importance of the surrounding structure on electrophilicity.…”
Section: Dually Activated Michael Acceptorsmentioning
confidence: 98%
“…33c Variable temperature NMR also demonstrated the reversibility of the reaction, as 411 was regenerated upon heating of the DTT- 411 adduct. 33c Other cyanoenones, such as tricyclic TBE-31 ( 434 ) 149 and monocyclic compounds 435-437 , 150 have shown similar reactivity towards thiols using the same UV and 1 H NMR methods (Figure 35). Surprisingly, compounds 439-440 showed no reactivity with DTT and 441-442 showed greatly reduced reactivity requiring 10 equiv of DTT for adduct formation, thereby demonstrating the importance of the surrounding structure on electrophilicity.…”
Section: Dually Activated Michael Acceptorsmentioning
confidence: 98%
“…1 The oral administration of 1 indicated excellent oral bioavailability, and resulted in a dose-dependent induction of cytoprotective enzymes, NAD(P)H:quinone oxidoreductase 1 (NQO1), and glutathione S-transferase (GST) in the stomach, skin, and liver. 2 Furthermore, longterm (five days per week for four weeks) daily topical applications in small quantities (200 nmol) of 1 caused a robust systemic induction of the Keap1/Nrf2/ARE pathway and decreased 6-thioguanine incorporation into DNA of skin, blood, and liver of azathioprine-treated mice, indicating extraordinary bioavailability and efficacy. 3 Tricyclic compound 1 is orally highly active against aflatoxininduced liver cancer in rats.…”
mentioning
confidence: 99%
“…We have previously shown that cyanoenones react with cysteine residues in Keap1, the main negative regulator of Nrf2. 6,7,14 In a variety of cell lines and animal tissues, we have demonstrated that Nrf2 activation by cyanoenones leads to the coordinate transcriptional upregulation of NQO1 together with other Nrf2-target genes, such as multiple isoforms of glutathione S-transferase (GST), heme oxygenase 1, -glutamyl cysteine ligase catalytic (GCLC) subunit, as well as an ARE-luciferase reporter, a direct readout of Nrf2-mediated transcription. 6,7,14 Furthermore, Nrf2 is required for the NQO1 inducer activity of cyanoenones as NQO1 induction is not observed in Nrf2-deficient cells.…”
mentioning
confidence: 99%
“…6,7,14 In a variety of cell lines and animal tissues, we have demonstrated that Nrf2 activation by cyanoenones leads to the coordinate transcriptional upregulation of NQO1 together with other Nrf2-target genes, such as multiple isoforms of glutathione S-transferase (GST), heme oxygenase 1, -glutamyl cysteine ligase catalytic (GCLC) subunit, as well as an ARE-luciferase reporter, a direct readout of Nrf2-mediated transcription. 6,7,14 Furthermore, Nrf2 is required for the NQO1 inducer activity of cyanoenones as NQO1 induction is not observed in Nrf2-deficient cells. 6,7 The electron affinity of these new compounds can be calculated via the energy of their lowest unoccupied molecular orbital, E (LUMO) in eV, and was quantified at two quantum mechanical levels: the semiempirical AM1, 16 and the density functional theory (DFT) 17 (see Table 1).…”
mentioning
confidence: 99%
See 1 more Smart Citation